2011
DOI: 10.1159/000329326
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Advanced-Stage Endometrial Cancer in Surgical Specimens from Patients with Complex Endometrial Hyperplasia with Atypia

Abstract: Objectives: To determine the incidence of endometrial cancer in patients undergoing hysterectomy for atypical complex endometrial hyperplasia and to study the risk of advanced endometrial cancer that may be associated with extra-uterine disease. Methods: A retrospective chart review was performed of the records of all women who underwent hysterectomy for a preoperative diagnosis of complex hyperplasia with atypia from two teaching hospitals between 1999 and 2006. Demographic and clinical variables were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Eddib et al, found out that; the incidence of endometrial cancer in patients undergone hysterectomy after being diagnosed with atypical endometrial hyperplasia was 17% and none of them was observed to have advanced tumour of more than grade 2 or stage 1B [17]. In similar study done by Rakha et al, suggested that patients who undergone hysterectomy due atypical endometrial hyperplasia and diagnosed with endometrial cancer; their tumours are endometrioid in morphology, early staged, low-graded and show good prognosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…Eddib et al, found out that; the incidence of endometrial cancer in patients undergone hysterectomy after being diagnosed with atypical endometrial hyperplasia was 17% and none of them was observed to have advanced tumour of more than grade 2 or stage 1B [17]. In similar study done by Rakha et al, suggested that patients who undergone hysterectomy due atypical endometrial hyperplasia and diagnosed with endometrial cancer; their tumours are endometrioid in morphology, early staged, low-graded and show good prognosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…ACH is a well-known precursor of EC [6,14,15,16], being associated with progression to EC in 29% of all cases [4]. The usual surgical treatment for ACH is simple hysterectomy with or without BSO.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a coexistent carcinoma may alter the surgical treatment approach. In addition, 20% of patients with these type I tumours, that develop out of endometrial hyperplasia, with, a presumed good outcome, present with recurrent disease [ 8 , 9 , 14 ]. Understanding of the progression from AH to EC might contribute to improved selection for hormonal treatment for fertility preservation for young patients, as well as for patients that are not suitable for surgery due to comorbidity.…”
Section: Introductionmentioning
confidence: 99%